An Efficient ZrCl4 Catalyzed Aza-Michael Addition Reaction: Synthesis of C-Linked Carbo β3-Amino Acids - Damera, Krishna; Reddy, Katta L.; Sharma, Gangavaram V.M. (Letters in Organic Chemistry, 2009)
A mild aza-Michael protocol has been developed using ZrCl4 as catalyst on α, β-unsaturated esters and nitriles. The aromatic amines were found to give the products with ease. The ZrCl4 mediated route was compatible with acid sensitive carbohydrate esters and provided an efficient method to prepare C-linked carbo β3-amino acids (β3-Caa).
Keywords: foldamers